Luminance and thresholding limitations of virtual reality headsets for visual field testing - Changseok Lee; Liam Redden; Vivian Eng; Brennan Eadie (PLoS ONE, 2025)
Purpose To investigate the luminance capacity and achievable threshold levels of commercially employed virtual reality (VR) devices for visual field testing. Methods This two-part study included (1) a literature review of VR headsets used for perimetry with luminance data extracted from technical specifications in publications and manufacturers; and (2) empirical evaluation of three most employed VR headsets in the literature using a custom virtual testing environment. Results Three most employed VR devices for visual field testing were Pico Neo, Oculus Quest, and HTC Vive. The maximum reported luminance was 250 cd/m2 for the HTC Vive Pro. Information on luminance measurement was not consistently available, reporting only handheld luminance meters. Empirical measurements show that handheld luminance meters significantly overestimate luminance compared to standard spectroradiometers. Measured luminance varies significantly across aperture size and decreases for peripheral stimuli up to 30 degrees peripherally. Assuming conventional background of 10 cd/m2, the best performance with lowest possible thresholding was with HTC Vive at 16dB, corresponding to luminance of 80 cd/m2 centrally. Oculus Quest 2 and Pico Neo 3 had minimum threshold of 20dB. Conclusion Commercially available VR devices do not meet luminance requirements or threshold sensitivities for visual field testing. Current VR technology is not designed—nor has the capacity—to threshold at mid-to-low dB ranges, which limits accuracy in diagnosing and monitoring defects seen in glaucoma. Translational Relevance: This study highlights the technical limitations of current commercially available VR devices for visual field testing and significant variables in evaluating luminance performance in these devices.